(untitled) (Al-Academy, 2017)
The audio-visual arts are considered modern arts compared to theater, plastic arts, and music. It proved its distinguished presences among other arts. It was capable of forming a huge audience and took television from cinema, literature, theater, type of narration, and narrative instructor. Also, it took symbolism and metaphorical repetition from literature. As for the importance of the functions that repetition has the research concentrated on the importance of function of repetition in deeping the esthetic meaning in television drama. The research was limited by:1.Objective limit: functions of repetition in deeping the esthetic meaning in series of (Harem Al-Sultan).2.Place where it was showed: series of (Harem Al-Sultan) part four on Nesima Tunisian channel.3.Time where it was showed: production of series (Harem Al-Sultan) was broadcasted on Nesima network channel in 2015.4.Identifying terminologies: repetition – esthetic- esthetic meaning.The second chapter contained subjects about rhetorical image and subject about imagery repetition. In chapter three and within the procedures of the research, the researchers depended on analytical descriptive method. As for the research sample it was part four of series of (Harem Al-Sultan). The research tool it depended on special indicators of theoretical section. It was modified after being viewed to experts and its final form came out:1.Means of connecting scenes and events.2.The increasing effect of growing events and conflict.3.Alerting tool separating the receiver from emotional reactions.4.Repeated stops to separate between the stage and another of events.5.Analytical job which allows the receiver to get deep into analysis and explanation of events.6.Mass media concentration by relying on filming techniques, montage, light, decoration, costumes, etc